School-Based HIV/STD Testing Behaviors and Motivations Among Black and Hispanic Teen MSM: Results From a Formative Evaluation - Morris, Elana (J Sch Health, 2016)
BACKGROUND: This evaluation explores experiences with, and motivations for, human immunodeficiency virus (HIV) and sexually transmitted disease (STD) testing among black and Hispanic school-aged young men who have sex with men (YMSM). METHODS: Participants were recruited at community-based organizations that serve YMSM in New York City, Philadelphia, and San Francisco. Eligible participants were 13- to 19-year-old black or Hispanic males who reported attraction to or sexual behavior with other males and/or identified as gay or bisexual, and attended at least 90 days of school in the previous 18 months. Participants (N = 415) completed web-based questionnaires and/or in-depth interviews (N = 32). RESULTS: In the past year, 72.0% of questionnaire participants had been tested for HIV, 13.5% of them at school or school clinic. Participants reported that they would be more likely to get an HIV test if they could be tested close to or at school (34.4%), and 64.4% would use HIV testing if offered in schools. Most interview participants reported willingness to use school-based services if they were offered nonjudgmentally, privately, and confidentially by providers with experience serving YMSM. CONCLUSION: Schools can provide opportunities to make HIV and STD testing accessible to school-aged YMSM, but the services must be provided in ways that are comfortable to them.